Conceptions of Portuguese Science Teachers on the Concept of Ecoethics - Luísa Carvalho; Luís Dourado; Maria José Varandas (MDPI AG, 2023)
Ecoethics is a philosophical subject that studies the moral relationship of human beings concerning the environment and its non-human components. Education for ecoethics addresses issues of how to live, how to make environmental choices, and how to think about the consequences of human activities. It is important that, firstly, the concept of ecoethics is clear to all involved, including teachers and students. Knowing that teachers' conceptions strongly influence their practice, and since no studies with teachers in active service were found, it was considered pertinent to investigate the conceptions of Portuguese Biology and Geology teachers about the concept of ecoethics. For data collection, a questionnaire was applied at a national level, with a related open-ended question. Categories of analysis were defined a priori and then the responses were classified based on those categories. The main results show that most respondents define ecoethics as ethics applied to the environment; almost a tenth relate the concept to issues concerning the preservation of life or the quality of life. Given the influence of teachers on students' education, a focus on teachers' training in ecoethics is essential as a starting point for an effective approach to ecoethics issues that can contribute to solving environmental problems.